Environmental communication strategy against deep-sea tailings disposal in Morowali - Lampe, Ilyas; Yusuf, Anggra; Kudratullah, Kudratullah; Saputra, Gemilang Bayu Ragil (Faculty of Communication Sciences Universitas Padjadjaran, 2024)
Environmental communication movement against Deep-Sea Tailings Placement (DSTP) permit for nickel mine waste of Indonesia Morowali Industrial Park (IMIP) skyrockets in response of DSTP issue. One example of the Non-Government Organization that pushed this movement is Jaringan Advokasi Tambang (JATAM), especially JATAM Sulteng. This movement is crucial considering the increase of nickel mining operations due of ellectronics demand, either for transportation or telecommunication purposes. From our initial observations, we concluded that this movement stands on discourse management of nickel mining, waste mangement and its effects to the environment. Thus, this study was done to discern what environmental communication strategy JATAM Sulteng choose to disseminate informations on the effects of nickel mining and processing of IMIP which also included on how they pushed the movement against DSTP on Morowali sea. This study was done through qualitative descriptive – case study approach. Data were collected through observation on publications, in-depth interview with three informants from JATAM Sulteng and document study. The results shows that the main stratagem choosen was to push the discourse of environmental degradation due to DSTP. The environmental degradation was then connected to the livelihood of the communities surrounding the mine and coastal communities adjacent to the DSTP sites. Supporting strategies for information dissemination also included focus group discussion (FGD), various critical essays, fact sheets and organizational press releases through official websites, mass media and social media, natural resources discussion forums, demonstrations and submission of petitions to the government and nickel extractive industry investors.